2016
DOI: 10.1016/j.schres.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of positive symptoms of psychosis in suicidal ideation among adults diagnosed with schizophrenia

Abstract: Background Suicide is among the leading causes of death for adults diagnosed with schizophrenia, with risk estimates being over eight folds greater than the general population. While the majority of research to date focuses on the role of symptoms of depression in suicide risk, there is a lack of consensus and understanding of the relationship between positive symptoms of psychosis and both suicidal ideation and attempt. The current study examined pathways of influence between symptoms of depression, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
3
15
0
2
Order By: Relevance
“…We also found relationships between HDL-C and anxiety, depression, and psychotic symptoms. Previous studies reported that the increase of positive symptoms as well as the symptoms of depression can increase the risk of suicidal ideation [28,29]. Further, Capron et al reported that anxiety can amplify the stress response, which in turn can increase the suicidal tendency [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found relationships between HDL-C and anxiety, depression, and psychotic symptoms. Previous studies reported that the increase of positive symptoms as well as the symptoms of depression can increase the risk of suicidal ideation [28,29]. Further, Capron et al reported that anxiety can amplify the stress response, which in turn can increase the suicidal tendency [33].…”
Section: Discussionmentioning
confidence: 99%
“…The Positive and Negative Syndrome Scale (PANSS) was employed to find whether there is a connection between suicide attempt and psychotic symptom in patients with MDD or not, because the independent increase of positive symptoms of psychosis as well as the symptoms of depression can lead to the increase of suicidal ideation [28,29]. Each item is scored on a 7-point scale based on the level of psychopathology.…”
Section: Collection and Evaluation Of Socio-demographic And Clinical mentioning
confidence: 99%
“…This finding is in line with previous studies, which have shown that experiences of suspiciousness may serve as a psychosis‐specific risk factor for suicide in psychotic patients (Bolton et al, ; Johnson et al, ; Palmier‐Claus et al, ; Taylor et al, ). Suspiciousness has been found to be associated with depressed mood, one of the most well‐established risk factors for suicide, in patients with overt psychosis (Bornheimer, ; Freeman et al, ; Messias, Kirkpatrick, Ram, & Tien, ). However, suspiciousness also seems to play an independent role beyond depression in the formation of suicidal ideation through various psychological processes including catastrophizing (Startup, Freeman, & Garety, ), threat beliefs (Freeman, Garety, Kuipers, Fowler, & Bebbington, ) and negative self‐cognitions (Collett, Pugh, Waite, & Freeman, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been mixed findings on whether the positive symptoms of schizophrenia contribute to the increased risk of suicide. Several studies have shown that the risk for suicide in patients with schizophrenia is significantly associated with the presence of psychotic symptoms, including delusions and hallucinations (Bertelsen et al, 2007;Bornheimer, 2016;Bornheimer & Jaccard, 2016;Nordentoft et al, 2002;Tarrier et al, 2006;Taylor et al, 2010), though this is not always the case (Hawton et al, 2005;Verdoux et al, 2001;Walsh et al, 2001). Since experiences of delusions and hallucinations may serve as a specific risk factor for suicide in affected individuals, recently developed psychological models of suicide have attempted to incorporate the impact of positive psychotic symptoms on the mind underlying suicidal ideation (Bolton, Gooding, Kapur, Barrowclough, & Tarrier, 2007;Bornheimer & Nguyen, 2016;Johnson, Gooding, & Tarrier, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hopelessness, which is considered an empirically established characteristic of depression, has been reported to be an even greater risk factor for suicidal behavior than is depression (Bornheimer, ; Popovic et al., ). The Beck Hopelessness Scale (BHS) is a 20‐item true–false self‐report instrument used to assess the degree of pessimism exhibited by a person (Beck & Steer, ).…”
Section: Methodsmentioning
confidence: 99%